Ezetimibe potently reduces vascular inflammation and arteriosclerosis in eNOS-deficient ApoE ko mice - Kuhlencordt, Peter J.; Padmapriya, P.; Rützel, S.; Schödel, Johannes; Hu, K.; Schäfer, A.; Huang, P. L.; Ertl, G.; Bauersachs, J. (Atherosclerosis, 2009)
Objective: Hypercholesterolemia is associated with decreased vascular nitric oxide bioavailability and deletion of endothelial nitric oxide synthase (eNOS) markedly accelerates atherosclerosis development in apolipoprotein E knockout (apoE ko) mice. The current study tests whether atheroprotection provided by a lipid lowering therapy with Ezetimibe depends on eNOS. Methods/results: ApoE ko and apoE/eNOS double ko (dko) mice received a high fat diet with or without 0.05% Ezetimibe. Ezetimibe significantly reduced plasma cholesterol concentrations and atherogenic lipoproteins in both genotypes to a similar extent. Moreover, the drug reduced vascular inflammation, as it significantly reduced vascular cell adhesion molecule-1 (VCAM-1) expression and vascular CD14 expression, a marker for mononuclear cell infiltration, in both genotypes. Neither NOS protein expression nor vascular reactivity of aortic rings was changed in apoE ko mice following Ezetimibe treatment. Significant lesion reduction was seen in Ezetimibe-treated male and female apoE ko and apoE/eNOS dko animals (p ≤ 0.05). Interestingly, the drug-mediated additional atheroprotection in male apoE ko, compared to male eNOS dko mice, suggesting that lipid lowering does provide additional eNOS-dependent atheroprotection in this experimental group. Conclusion: Lipid lowering with Ezetimibe potently reduces atherosclerosis and vascular inflammation independent of eNOS. Moreover, Ezetimibe did not exert any effects on eNOS protein expression or enzyme activity. However, additional atheroprotection by Ezetimibe was observed in eNOS competent apoE ko mice, suggesting that some of the drug's anti-atherosclerotic effects are mediated by the eNOS pathway. © 2008 Elsevier Ireland Ltd. All rights reserved.
CRIS-Team Scopus Importer:2024-05-13
Keywords: Atherosclerosis; Endothelial activation; Endothelial vasodilator function; Ezetimibe; Nitric oxide